Correlation between Achievement Motivation with Academic Stress among Student of PLB FKIP UNS Year 2018 who took Home Classes During Covid-19 - Nabilah Nur Hasya Huwaida Fauziyyah; Tias Martika (Journal of Disability, 2021)
This research aims to know the correlation between achievement motivation with academic stress on student of PLB FKIP UNS who takes the class from home during the Covid-19 pandemic. The population in this study was all students of PLB FKIP UNS. The sample in this study were 77 students of PLB FKIP UNS year 2018. The sampling technique used in this study was saturation sampling technique. This research is a quantitative research with correlational research type. The data collection techniques in this study used a scale of achievement motivation and scale of academic stress. The data analysis techniques used in this study was Pearson Product Moment correlation. The results of this study have a value (r)=-0.15 and correlation coefficient of 0.896. Based on the results of data analysis, it can be concluded that there is no significant relationship between achievement motivation with academic stress on student of PLB FKIP UNS year 2018 when taking class from home during the Covid-19 pandemic.